(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Cutaneous adnexal tumors (CATs) are a diverse group of neoplasms originating from the adnexal structures of the skin, including hair follicles, sebaceous glands, eccrine glands, and apocrine glands. These tumors demonstrate varied histopathological differentiation and clinical presentations, ranging from benign lesions to rare malignant counterparts. Accurate diagnosis and classification are essential because of their diverse biological behavior and potential association with syndromic conditions. Aim & Objectives: To evaluate the clinicopathological spectrum of cutaneous adnexal tumors with respect to age, sex, anatomical site, histological differentiation, and tumor type. Materials & Methods: This retrospective descriptive study included 48 histopathologically confirmed cases of cutaneous adnexal tumors. Clinical details were retrieved from medical records. Formalin-fixed, paraffin-embedded tissue sections were stained with hematoxylin and eosin and examined microscopically. Tumors were categorized according to their line of differentiation. Statistical analysis was performed using descriptive statistics and the Chi-square test, with p < 0.05 considered statistically significant. Results: Most cases occurred in the 21–40 years age group, with a slight male predominance. The head and neck region were the most affected site (64.6%). Follicular differentiation was the predominant histological type (64.6%), followed by eccrine and apocrine differentiation. Trichilemmal cyst was the most common diagnosis, accounting for 37.5% of cases. A statistically significant association was observed between anatomical site and differentiation pattern (p < 0.05). Most tumors were benign in nature. Conclusion: Cutaneous adnexal tumors are predominantly benign lesions with a strong predilection for the head and neck region and follicular differentiation. Histopathological examination remains the cornerstone for accurate diagnosis and classification of these tumors.